Developing self and peer assessment to improve student's appreciative critical ability in learning drama appreciation - Rohmah, Khafidatur; Priyatni, Endah Tri; Suwignyo, Heri (Graduate School, Universitas Negeri Yogyakarta, 2021)
This study aims to develop self and peer assessment instruments to improve students' critical and appreciative abilities in learning drama appreciation. This research was conducted by following the ADDIE model development steps: needs analysis, product design, product development, product implementation, and product evaluation. There are two types of data in this study: qualitative data and quantitative data. Quali-tative data are in the form of suggestions and comments from assessment experts, literature experts, and drama appreciation learning experts, as well as students, while quantitative data are in the form of scores obtained from assessment experts, literature experts, and drama appreciation learning experts, as well as students. Both data were obtained through questionnaire guidelines. The data obtained were then analyzed. Qualitative data were analyzed using descriptive analysis techniques, while quantitative data using quantitative descriptive analysis techniques. The analysis technique used shows that the product developed can increase students' critical appreciative abilities by getting an average percentage of 8.3% for the display aspect, 9.7% for the product content aspect, and 90.4% for the language aspect. The three averages were obtained from assessment experts, literary experts, and drama appreciation learning experts. When testing the product, students got an average score of 82.2% on the aspect of students' impressions of the use of self and peer assessment in increasing students' critical appreciation skills in learning drama appreciation and 80.4% on the aspect of practicality and ease of self and peer assessment for improving students' appreciative critical abilities in drama appreciation learning.